The flora of Newfoundland, Labrador and St. Pierre et Miquelon [electronic resource] : part III - Waghorne, Arthur C. (Arthur Charles); Nova Scotian Institute of Science. ([S.l. : s.n., 1898)
Cover title. "Read May 9th, 1898"--p. 35. "From the Transactions of the Nova Scotian Institute of Science, vol. IX, session, 1897-8." Electronic reproduction. Mode of access: Internet. 44